2015
DOI: 10.5489/cuaj.3094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on functional and oncological outcomes in radical perineal prostatectomy

Abstract: Introduction:We evaluated the impact of obesity on perioperative morbidity, functional, and oncological outcomes after radical perineal prostatectomy (RPP). Methods: A total of 298 consecutive patients underwent RPP at our institution. Patients were categorized into 3 groups based on their body mass index (BMI): Normal weight <25 kg/m 2 (Group 1), overweight 25 to <30 kg/m 2 (Group 2), and obese ≥30 kg/m 2 (Group 3). We compared the groups with respect to perioperative data, postoperative oncologic, and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Authors from Turkey reported that obesity did not correlate with worse oncological and functional outcomes in patients who underwent radical perineal prostatectomy. 2 The present study has shown that obesity is associated with upgrading (p=0.043) and the rate of locally advanced disease HGPCA was higher in obese patients than in the others.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…Authors from Turkey reported that obesity did not correlate with worse oncological and functional outcomes in patients who underwent radical perineal prostatectomy. 2 The present study has shown that obesity is associated with upgrading (p=0.043) and the rate of locally advanced disease HGPCA was higher in obese patients than in the others.…”
Section: Discussionsupporting
confidence: 46%
“…The positive surgical margin rate was reported between 6.1 and 53% in the studies. 2,11 There was signifi cant difference for positive surgical margin between BMI categories 11 , the other study revealed that the rate of positive surgical margin is lower (6.1%) in patients with BMI >30 kg/m 2 than BMI <25 kg/m 2 (6.9%) with no signifi cant difference. The present study revealed that the positive surgical margin is lower in obese men than in the others with an incidence of 5.55%.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations